Quality Control Evaluation of Maska Mruganka RASA An Ayurvedic Metallic Formulation - Biradar, Shivanand T (International Journal of Pharmaceutical & Biological Archive, 2014)
Quality Control Evaluation of Maska Mruganka RASA An Ayurvedic Metallic Formulation